2019
DOI: 10.1371/journal.pgen.1007941
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin receptor Aa regulates proliferation and differentiation of Erb-dependent pigment progenitors in zebrafish

Abstract: Skin pigment patterns are important, being under strong selection for multiple roles including camouflage and UV protection. Pigment cells underlying these patterns form from adult pigment stem cells (APSCs). In zebrafish, APSCs derive from embryonic neural crest cells, but sit dormant until activated to produce pigment cells during metamorphosis. The APSCs are set-aside in an ErbB signaling dependent manner, but the mechanism maintaining quiescence until metamorphosis remains unknown. Mutants for a pigment pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…In zebrafish, endothelin signalling is directly required in iridophores for their development and proliferation; iridophores indirectly promote and sustain melanophore development 32 . Several paralogs exist for endothelin receptors and ligands 74 , only one of each is specifically involved in patterning 7 , 29 , 73 , 75 . Indeed, it has been shown that in D. nigrofasciatus , due to cis-regulatory changes, the expression of the secreted ligand Endothelin 3b (Edn3b) is lower than in D. rerio 73 .…”
Section: Discussionmentioning
confidence: 99%
“…In zebrafish, endothelin signalling is directly required in iridophores for their development and proliferation; iridophores indirectly promote and sustain melanophore development 32 . Several paralogs exist for endothelin receptors and ligands 74 , only one of each is specifically involved in patterning 7 , 29 , 73 , 75 . Indeed, it has been shown that in D. nigrofasciatus , due to cis-regulatory changes, the expression of the secreted ligand Endothelin 3b (Edn3b) is lower than in D. rerio 73 .…”
Section: Discussionmentioning
confidence: 99%
“…By sampling individual cell transcriptomes across NC-derived lineages, our study complements prior investigations of lineage relationships, morphogenetic behaviors, genetic requirements, and spatial and cell-type-specific gene expression profiles (Eom et al, 2015; Irion et al, 2016; Johnson et al, 1995; Kelsh et al, 2017; McMenamin et al, 2014; Parichy and Spiewak, 2015; Singh et al, 2016; Singh et al, 2014). Multipotent progenitors that give rise to adult melanophores, some xanthophores, and iridophores are established in the embryo and reside within peripheral nerves as development progresses (Budi et al, 2011; Budi et al, 2008; Camargo-Sosa et al, 2019; Dooley et al, 2013a; Singh et al, 2016). As the adult pattern forms, some of these cells migrate to the hypodermis where they differentiate and integrate into dark stripes or light interstripes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, our finding that metformin, which itself had little effect on pigmentation, demonstrates opposing effects on melanocyte production when combined with GABA or TSPO pathway compounds suggests that melanocyte development must integrate both local and systemic signals during pigmentation. In addition to local and systemic cues, MSCs also appear to respond to spatial cues, as recent work indicates the ednraa RTK pathway regulates MSC quiescence specifically in the ventral trunk of larval zebrafish (Camargo‐Sosa et al, ). In the future, it will be interesting to determine how GABA and TSPO function integrate with ednraa activity to regulate MSC quiescence and activation.…”
Section: Discussionmentioning
confidence: 99%